Implementation of Asset Management Policy in Tana Tidung Regency - Fitrianah Fitrianah; Tuty Maria Wardiny; Entang Adhy Muhtar (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This research aims to analyze and describe the implementation of regional asset management policies in the Tana Tidung Regency as well as the factors inhibiting the implementation of regional asset management policies. The policy implementation theory used by Van Meter van Horn consists of policy standards and targets; resources, communication between organizations, characteristics of implementing agents; social, economic, and political conditions, and the attitude of implementing agents. The research method used is qualitative with a case study approach. Data collection techniques through interviews, observation, and documentation. The informants in this research were the Head of the BPKAD Agency, the BPKAD Secretary, the Head of Asset Management, the Regional Property Management Staff, and the Deputy Chair of the Tana Tidung Regency DPRD. The results of the research regarding the implementation of regional asset management policies in Tana Tidung Regency, namely 1) Policy standards and targets, namely BKPAD Tana Tidung Regency carries out management in accordance with regional asset management principles and procedures starting from planning to coaching, supervision and control; 2) Resources, namely the management of regional assets in Tana Tidung Regency are quite adequate, such as budget and facilities and infrastructure, although the availability of human resources is still relatively low because in terms of quantity BPKAD only has 49 human resources while the workload is more Lots; 3) Communication between organizations, namely BPKAD Tana Tidung Regency, is carried out through meetings and coordination between OPDs of Tana Tidung Regency regularly and consistently; 4) Characteristics of the implementing agent, namely in the implementation of regional asset management in BPKAD, namely the capacity of BPKAD and the autonomy possessed by BPKAD as an official or institution that has authority in managing regional property; 5) Social conditions, namely the economy and politics, are running effectively, this is because there are interest groups providing support for policy implementation; 6) The attitude of the executors (deposition), namely as agents managing regional property, is demonstrated through BPKAD's responsibility in managing regional property, carrying out control and supervision of assets through users by monitoring and controlling use, utilization, transfer, administration, maintenance and security. regional property under its control